An Object Oriented Approach for Business Process Reengineering - Alhussein Musmar, Abdelmajid Omer (2008)
Successful Business Process Reengineering (BPR) projects depend on the appropriate business process modeling techniques. On the other side, Information technology (IT) is considered as a key enabler of BPR. Since the object-oriented technique became the most common approach for implementing information systems, the object oriented approach to business process modeling seems to be the best way for more successful BPR projects. This work aims to develop a modeling method for BPR. This method should fill the gap between modeling business process and creating a supportive information system for the redesigned processes in BPR. The present work introduces BPR modeling method that links object orientation with business process modeling. The proposed method integrates an object-oriented modeling method (An Extended object-oriented modeling method) with object-oriented modeling language (Unified Modeling language UML). Design science methodology was used to develop the proposed modeling method. The proposed method was implemented into two types of business process case studies. The implementation showed a promising modeling technique for representing the business process and linking business process modeling with the development of the supportive information system.